Modern pedagogical opportunities of youth tourism - Ibragimova Venera Azadovna (Zien Journals, 2023)
This article discusses the modern pedagogical opportunities of youth tourism, in particular, educational tourism, a part of youth tourism that allows young people to learn many new things.
Keywords: Tourism; youth; travel; youth tourism